2013
DOI: 10.1177/0269216313483660
|View full text |Cite
|
Sign up to set email alerts
|

Informal hospice caregiver pain management concerns: A qualitative study

Abstract: Background Informal, unpaid, family caregivers provide much hospice care in the United States. These caregivers suffer physically, psychologically, emotionally, and socially from the burden of caring. The most often identified area of caregiver burden is the management of end-of-life pain. However, little empirical evidence exists of effective interventions to help caregivers manage end-of-life pain, and issues surrounding caregiver pain management remain vague and undefined. Understanding these concerns will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 35 publications
1
69
0
Order By: Relevance
“…45 These issues were accentuated when patients were not able to verbalize their pain. 39 Further issues with administration were cited by FCGs with regard to how medicines were to be administered. For example, an FCG in one study reported being unable to give medications because the increments of the dropper did not match the written prescription given by the doctor ( 45 : p. 120).…”
Section: Administrationmentioning
confidence: 99%
“…45 These issues were accentuated when patients were not able to verbalize their pain. 39 Further issues with administration were cited by FCGs with regard to how medicines were to be administered. For example, an FCG in one study reported being unable to give medications because the increments of the dropper did not match the written prescription given by the doctor ( 45 : p. 120).…”
Section: Administrationmentioning
confidence: 99%
“…Some qualitative studies have shown that caregivers are often unable to assess pain, are overly concerned with side effects, are inexperienced in administering analgesics, and found communicating with medical professionals difficult. 46 Because the family caregiver's role in cancer pain management at home is crucial, helping them develop sufficient self-confidence and the capability to effectively assist professionals in cancer pain management should include establishing trusting relationships between all parties involved (patients, family caregivers, and medical professionals). 47 Educating family caregivers with respect to communicating with health professionals, improving analgesic regimen adherence, and the importance of maintaining the prescribed dosage may provide patients with more confidence in coping with pain management at home.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Kelley et al analyzed interviews with 29 family caregivers of patients with cancer receiving home hospice care from a mixed-methods clinical trial. 39 The interview data were analyzed using content analysis and organized to describe the pain management challenges faced by the hospice family caregivers. The barriers to effectively managing patients' pain caused by cancer for the family caregivers included caregivers' knowledge and skills in symptom and medication management, communication issues, patient-centric issues (pain assessment congruency between patients and family caregivers, well-being, mythical/religious/ethical/moral beliefs about pain control, inability to verbalize pain, etc), and caregiver-centric issues (function, cognition, mythical/religious/ethical/moral beliefs about pain control, self-efficacy in pain management, concurrent responsibility, etc).…”
Section: Engagement and Communicationmentioning
confidence: 99%
“…The barriers to effectively managing patients' pain caused by cancer for the family caregivers included caregivers' knowledge and skills in symptom and medication management, communication issues, patient-centric issues (pain assessment congruency between patients and family caregivers, well-being, mythical/religious/ethical/moral beliefs about pain control, inability to verbalize pain, etc), and caregiver-centric issues (function, cognition, mythical/religious/ethical/moral beliefs about pain control, self-efficacy in pain management, concurrent responsibility, etc). 39 McPherson et al used a qualitative descriptive approach with thematic analysis to explore the cancer pain perceptions and experience of older adults and their family caregivers. 40 Eighteen older adults with advanced cancer receiving palliative care at home and 15 family caregivers participated in semistructured interviews to express their experience of patients' pain.…”
Section: Engagement and Communicationmentioning
confidence: 99%